PAW CAWABUP PARIGI MOUTONG 2011-2013 (Analisis Wacana Kritis Tentang Pemberitaan Cawabup Parigi Moutong Pada Harian Mercusuar dan Radar Sulteng 2011 Edisi September âJanuari 2012) - , MUHAMMAD WAHID ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Studies on PAW Cawabup Parigi Moutong 2011-2013 through print media discourse analysis on the daily news Mercusuar and Radar Sulteng edition september 2011 - January 2012, shows that the role of the print media is still very necessary in a political campaign by all the leading figures who will chair leaderships, including in Parigi - Moutong district of Central Sulawesi. Both the mass media Daily Radar Sultemg and Daily Mercusuar, is a medium that is most liked by the people of Central Sulawesi, the oldest newspaper has a readership of fanatical among the Muhammadiyah, as it is considered as partners in the struggle Muhammadiyah socialize in Central Sulawesi. The coverage both give a different color, both on the meaning of news as well as news on the context. Daily Mercusuar in the presentation emphasizes the aspects of the public service, but used to include news values that lead to the interest groups that carried by one of the candidates of political parties. This is reflected in the headline of administration, the mention of the name repeatedly, appearing as part of the clan is expected to affect the image of the candidate, and even the natives of discourse and representation areas become very widely reported. This attitude is also supported by the editorial policy to motivate journalists assigned to cover. Daily Radar Sulteng, also remains a conduit of information to the public, but rather in the context of the development of customized news and the phenomenon is happening. The volume is also not as routine preaching what the Daily Mercusuar. Without realizing activities both media coverage has become very important in the present discourse, so that what is done over the Mercusuar Daily confrontational aspects of the news, it is more on the emotional connection between one of the candidates with the leadership of this medium. It can not be denied, it does not directly create the discourse impressed subjective.